La formación en las universidades pedagógicas. Un punto de encuentro (2016)
This article presents an overview on the history of teacher training in Latin America and on the educational reform currently being implemented in Mexico. It examines the many political considerations that have directly affected teacher training institutions, since in different reflections about the quality of education, teachers are recognized as the foundation of the same. Therefore, the participation of these transforming agents is crucial in the construction and legitimization of policies in order to achieve success in the struggle to improve education.